2023
DOI: 10.31897/pmi.2023.6
|View full text |Cite
|
Sign up to set email alerts
|

Development of methodology for economic evaluation of land plots for the extraction and processing of solid minerals

Abstract: The Russian economy has a pronounced resource specialization; in many regions, subsoil use is a backbone or one of the main areas of the economy. In these conditions, the improvement of the methodology for the economic evaluation of lands on which mining enterprises are located is of particular relevance. On the basis of the existing experience in assessing industrial land, the authors present a developed methodology for determining the cadastral value of land plots where mining enterprises are located, taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…However, the value of REC = 0.244 is statistically insignificant (p > 0.05), that is, there is insufficient evidence to assert that this indicator has a non-random character. The results obtained are similar to several works; for example, [72,85,86] have found that the p-values of GDP 2 , GDP 1,2,3 and GDP are statistically significant (5%) for Iran and BRICS countries, respectively; and statistical significance (5%) for FDI indicators [85] and FDI, NRR and REC [86] was found. In [79], they found that FDI and TO are statistically insignificant and have an inverse relationship with the indicator of environmental degradation for Russia.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, the value of REC = 0.244 is statistically insignificant (p > 0.05), that is, there is insufficient evidence to assert that this indicator has a non-random character. The results obtained are similar to several works; for example, [72,85,86] have found that the p-values of GDP 2 , GDP 1,2,3 and GDP are statistically significant (5%) for Iran and BRICS countries, respectively; and statistical significance (5%) for FDI indicators [85] and FDI, NRR and REC [86] was found. In [79], they found that FDI and TO are statistically insignificant and have an inverse relationship with the indicator of environmental degradation for Russia.…”
Section: Resultssupporting
confidence: 89%
“…According to the Cheddock scale, there was a positive and observable relationship between L(GHG) and L(GDP), L(GDP) 2 and L(GDP) 3 ; a positive and moderate relationship between L(GHG) and L(NRR); a negative and weak relationship between L(GHG) and L(FDI); a negative and observable relationship with L(TO) and a negative and moderate relationship between L(GHG) and L(REC). Additionally, there is a strong positive relationship between the regressors L(GDP), L(GDP) 2 and L(GDP) 3 . All GDP values have a marked and negative relationship with L(REC), moderate and positive with L(NRR) and weak and positive with L(FDI).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The company's activities without the presence of reserves and resources in the subsoil and development rights have no prospects for either economic development or economic growth [34]. Regulation of access to resources can be presented as one of the industry tools for development and growth [35]. The main regulatory tools are subsoil use regimes, licensing, and standardization [36].…”
Section: Potential and Downside Factors Of Russian Companies' Successmentioning
confidence: 99%
“…Due to the obvious fact pointed by numerous researchers that "mineral resource complex" (Khrustaleva et al, 2021: 417) along with "mineral resources as natural capital" (Litvinenko et al, 2023: 95) and "a pronounced resource specialization" (Bykova et al, 2023) representing a clear-cut factor of a country's sustainable development, the segment of the mining engineering education should be given particular emphasis as a key factor of technological and scientific progress (Bergamo et al, 2022;Gutierrez-Bucheli et al, 2022;Sigahi, Sznelwar, 2023). Technical education "needs modern and sophisticated methods" (Skornyakova, Vinogradova, 2022: 100) to keep in line with the demands of the global labour market demand.…”
Section: Introductionmentioning
confidence: 99%